The Long Pentraxin 3 and Its Role in Autoimmunity (2009)
Objectives: To review the physiological and physiopathological roles of pentraxin 3 (PTX3), focusing on autoimmunity and vascular pathology. Methods: A systematic literature review using the keywords 'pentraxin 3,' 'innate immunity,' 'apoptosis,' 'autoimmunity,' and 'endothelial dysfunction' from 1990 to 2007 was performed. All relevant articles and pertinent secondary references in English were reviewed. Results: PTX3 has a large number of multiple functions in different contexts. PTX3 plays an important role in innate immunity, inflammation, vascular integrity, fertility, pregnancy, and also in the central nervous system. In innate immunity, its normal function is to increase the immune response to selected pathogens while also exerting control over potential autoimmune reactions. It maintains a tightly homeostatic equilibrium in the local immune microenvironment by avoiding an exaggerated immune response and controlling peripheral tolerance to self-antigens. In contrast, in some autoimmune diseases, PTX3 appears to be involved in the development of autoimmune phenomena. A possible explanation for these apparent paradoxical functions may be related to the highly polymorphic PTX3 gene. Conclusion: PTX3 is physiologically a protective molecule. However, in several autoimmune diseases PTX3 appears to facilitate the development of autoimmunity. The PTX3 gene could influence the development of autoimmune reactions and vascular involvement in human pathology. © 2008 Elsevier Inc. All rights reserved.